Material concreto y el pensamiento lógico matemático en los niños de preparatoria de la Unidad Educativa Fiscal Dr. Manuel Agustín Cabrera Lozano de la ciudad de Loja, periodo 2024-2025 - Quito Pinta, Janina Lilibeth (2025)
Mathematical logical thinking is developed through interaction with the environment, allowing the child to explore the environment around him. Thus, one of the resources used for the acquisition of mathematical skills are concrete materials that promote a more meaningful learning. Therefore, the objective of this research was to determine how concrete material strengthens the development of mathematical logical thinking in high school children of the Unidad Educativa Fiscal Dr. Manuel Agustín Cabrera Lozano of the city of Loja, period 2024-2025. For the development of the research, a non-experimental design was used, with a mixed approach that combined quantitative and qualitative, in addition to a descriptive scope; likewise, the inductive-deductive and analytical-synthetic methods were used to collect relevant information for the construction of the theoretical framework and the support of the research work. In turn, the observation technique and the Basic Mathematical Competence Test-3 were used to evaluate the level of development of mathematical logical thinking in children from five to six years of age, which yielded the following results: 4% of the children presented an average level of mathematical competence, 21% were below average, 8% were poor and 67% were very poor, showing that there was greater difficulty in aspects such as: counting, following numerical sequences, comparing quantities, solving addition problems and writing numbers. Through the bibliographic review it is concluded that concrete material allows children to create their own knowledge through manipulation and exploration with tangible objects, creating enriching learning experiences.